Digital business case: Scientific contributions for a digital framework from benefits realisation management - Santos, J. P.; Pereira, L. (International Journal of Management and Decision Making, 2024)
Nowadays, the pandemic situation has put several businesses in constant uncertainty, with additional concerns for professionals who aim to initiate or evaluate a project endeavour in the context of digital transformation. Thus, the constant market change needed a scientific approach to overcome such uncertainty. The new digital business case was raised with the intuit of providing a business case framework towards the new requirements and needs from professionals by adopting the concept of scientific management and incorporating several new mathematical and statistical methods. This tool was the natural evolution of the business case tool (BC Tool). In order to validate the effectiveness of this new tool, it was used to elaborate on the previous business case with the business case tool and apply the new scientific developments. The results have proven that the digital business case provides a more reliable, and comprehensive benefit and cost estimation analysis in the business case project evaluation.